'South Africa is Not an Accused': State (non) Co-operation with the ICC and the Case of the Arrest Warrants for President Omar al-Bashir (Strathmore Law Journal, 2017)
There is a confrontation between the International Criminal Court (ICC) and state parties, and at this particular point in time, the Republic of South Africa, in connection with the arrest warrants issued by the Court for the President of Sudan in 2009 and 2010. Between 13 and 15 June 2015, President Omar al-Bashir was present on the territory of South Africa for purposes of attending the 25th Ordinary Session of the Assembly of the African Union. Despite judgments from both the ICC upholding the obligation of South African authorities to arrest and surrender President Bashir and parallel domestic proceedings at the South African High Court in which authorities were ordered to prevent the departure of President Bashir from South African territory pending final judicial decision on whether the Government was required to execute the ICC arrest warrants, President Bashir nevertheless departed from the Waterkloof military air base on 15 June 2015, even as Government lawyers assured the High Court in a hearing on the same date that he was still in the country. Only after his plane had safely landed in Khartoum did the same lawyers then notify the High Court that he had left South Africa. This article will analyze this case in the following lines.